Climbing the Coffee Global Value Chain - Three Decades of Trade and Upgrading - Aoife Hanley; Wan-Hsin Liu; Finn~Ole Semrau; Dennis Görlich (Journal of International Development, 2025)
Developing countries frequently struggle to generate wealth from trade in agri-commodities such as coffee, where the end price of a cup of coffee sold in Berlin or New York returns only a fraction of the value to the actual coffee grower. With this in mind, we investigate this phenomenon using unique cross-border data for 280.167emyears (1991–2018), where coffee is represented in its various formats, from unprocessed `green' coffee beans to the roasted and soluble products. In so doing, we derive a measure of functional upgrading. Analogously, we report the extent to which countries upgrade their coffee production, adding value to their raw coffee exports (product upgrading). Our data reveal that many coffee cultivating countries are unable to capitalize on the boom in roasted coffee exports—losing out on the upswing in high-end consumption. Conversely, we find that Asian countries are more likely to climb the coffee GVC, while many African countries remain exporting green coffee. Interestingly, coffee cultivating countries with higher levels of industrialization and reduced distance to processing hubs, all things equal, are associated with higher value added. The coffee variety cultivated also plays a crucial role as does the trade policy pursued.
Keywords: 300; coffee; development; global value chain; trade; upgrading